Kounis syndrome following canned tuna fish ingestion*. Issue 2 (4th March 2017) - De Gennaro, Luisa; Brunetti, Natale Daniele; Locuratolo, Nicola; Ruggiero, Massimo; Resta, Manuela; Diaferia, Giuseppe; Rana, Michele; Caldarola, Pasquale
Abstract : Kounis syndrome (KS) is a complex of cardiovascular symptoms and signs following either allergy or hypersensitivity and anaphylactic or anaphylactoid insults. We report the case of 57-year-old man, with hypertension and history of allergy, referred for facial rash and palpitations appeared after consumption of canned tuna fish. Suddenly, the patient collapsed: electrocardiogram showed ST-elevation in inferior leads. The patient was transferred from the spoke emergency room for coronary angio, which did not show any sign of coronary atherosclerosis. A transient coronary spasm was therefore hypothesized and the final diagnosis was KS. To the best of our knowledge, this is one of the first cases of KS following the ingestion of tuna fish. KS secondary to food allergy has also been reported, and shellfish ingestion has been considered as one of the most active KS inducer foods. Canned tuna fish too is well known as an allergy inducer. Tuna fish allergy should be considered, however, within the context of scombroid food poisoning, also called histamine fish poisoning. Fish with high levels of free histidine, the enzyme substrate converted to histamine by bacterial histidine decarboxylase, are those most often implicated in scombroid poisoning. Inflammatory mediators such as histamine constitute the pathophysiologic basis of Kounis hypersensitivity-associated acute coronary syndrome. Patients with coronary risk factors, allergic reaction after food ingestion, and suspected scombroid poisoning should be therefore carefully monitored for a prompt diagnosis of possible coronary complications.